Double sequential external defibrillation for refractory ventricular fibrillation: The DOSE VF pilot randomized controlled trial. (May 2020) - Cheskes, Sheldon; Dorian, Paul; Feldman, Michael; McLeod, Shelley; Scales, Damon C.; Pinto, Ruxandra; Turner, Linda; Morrison, Laurie J.; Drennan, Ian R.; Verbeek, P. Richard
Abstract: Objectives: The primary objective was to determine the feasibility and safety of a cluster randomized controlled trial (RCT) with crossover comparing vector change defibrillation (VC) or double sequential external defibrillation (DSED) to standard defibrillation for patients experiencing refractory ventricular fibrillation (VF). Secondary objectives were to assess the rates of VF termination (VFT) and return of spontaneous circulation (ROSC). Methods: We conducted a pilot cluster RCT with crossover in four Canadian paramedic services including all treated adult OHCA patients who presented in VF and received a minimum of three successive defibrillation attempts. Each EMS service was randomly assigned to provide standard defibrillation, VC or DSED. Agencies crossed over to an alternate defibrillation strategy after six months. Results: 152 patients were enrolled. With respect to feasibility, 89.5% of cases received the defibrillation strategy they were randomly allocated to, and 93.1% of cases received a VC or DSED shock prior to the sixth defibrillation attempt. There were no safety concerns reported. In the standard group, 66.6% of cases resulted in VFT, compared to 82.0% in VC and 76.3% in the DSED group. ROSC was achieved in 25.0%, 39.3% and 40.0% of standard, VC and DSED groups, respectively. Conclusions: Our findings suggest the DOSE-VF protocol is feasible and safe. Rates of VFT and ROSC were higher in the VC and DSED than standard defibrillation. The results of this pilot trial will allow us to inform a multicenter cluster RCT with crossover to determine if alternate defibrillation strategies for refractory VF may impact clinical outcomes.